Growth and Cultivation of the Unusual Generalized Transducing Bacillus Bacteriophage SP-15 - Taylor, Martha J. (1971)
Additional properties of SP-15, a generalized transducing bacteriophage notable for the ability to transfer an unusually large fragment of deoxyribonucleic acid (DNA) to Bacillus subtilis and B. licheniformis, are presented together with improved methods that enhance its utility. Simple means have been found to provide the rigid control over moisture that is necessary for the assay of plaque-forming units (PFU). Reproducible procedures for propagating transducing phage, which depend upon an appropriate mixing of PFU with uninfected bacteria, have replaced less reliable methods that utilized infected spores. Transduction of B. subtilis W-23 increased linearly when MgSO(4) in recipient cell-SP-15 mixtures was increased from 0.005 to 0.03 m. Methods have been developed that protect SP-15 from the damaging effects of CsCl and of osmotic shock subsequent to dilution. Evidence that the PFU and transducing particles of lysates decay at the same slow rate during extended storage suggests that the decay is a result of damage to protein rather than to DNA. One-step growth experiments, in which SP-15 was propagated on B. subtilis W-23-S(r)/1 mg, indicated a latent period of 100 min, a rise period of 60 min, and a burst size of 25 to 34 PFU per infected cell. These findings suggest explanations for some of the technical difficulties SP-15 has presented.